The role of individual and contextual socioeconomic circumstances on mortality: analysis of time variations in a city of north west Italy. Issue 3 (13th February 2004) - Marinacci, C; Spadea, T; Biggeri, A; Demaria, M; Caiazzo, A; Costa, G
Abstract : Study objective: To evaluate the independent and mutual effects of neighbourhood deprivation and of individual socioeconomic conditions on mortality and to assess the trends over the past 30 years and the residual neighbourhood heterogeneity. Design: General and cause specific mortality was analysed as a function of time period, highest educational level achieved, housing conditions, and neighbourhood deprivation, using multilevel Poisson models stratified by gender and age class. Setting: The study was conducted in Turin, a city in north west Italy with nearly one million inhabitants and consisting of 23 neighbourhoods. Participants: The study population included three cohorts of persons aged 15 years or older, recorded in the censuses of 1971, 1981, and 1991 and followed up for 10 years after each census. Main results: Individual and contextual socioeconomic conditions showed an independent and significant impact on mortality, both among men and women, with significantly higher risks for coronary heart and respiratory diseases among people, aged less than 65 years, residing in deprived neighbourhoods (9% and 15% excess for coronary heart diseases, 20% and 24% for respiratory diseases, respectively for men and women living in deprived neighbourhoods compared with rich). The decreasing time trend in general mortality was less pronounced among men with lower education and poorer housing conditions, compared with their more advantaged counterparts; the same was found in less educated women aged less than 65 years. Conclusions: These results and further developments in the evaluation of impact and mechanisms of other contextual effects can provide information for both health and non-health oriented urban policies.